Perancangan Rusunami Di Kawasan Pantai Indah Kapuk Dengan Pendekatan Arsitektur Modern - Azriel Ahmad Baroky; Anggraeni Dyah Sulistiowati; Tri Endangsih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Population growth results in the need for housing. Based on the Central Bureau of Statistics (BPS), North Jakarta City has a population growth percentage increase of around 1% each year. As the population increases in urban areas, housing and open space must be given more attention because with population growth, the demand for housing and public open space is more qualified, but the existing land area is constant which causes limited land available, especially in urban areas. Pantai Indah Kapuk is a city intended as a tourist city so there are many destination tour as culinary and commercial development. Because of the many tourist facilities located in the Pantai Indah Kapuk area, which causes the number of workers needed, the solution that can be given is to build a vertical residential house as a property right, namely Flats which is focused on workers who want to live there. With the emphasis of the theme and rationale directed at the design of the Flats building with a Modern architectural approach with the main objective of giving the impression of not being outdated and prioritizing the function of the Flats itself and having social facilities and public facilities to support the residents who live in the Flats.